Photocatalytic Decomposition of Nonylphenol in Aqueous Solutions by ZnO Nanoparticles - Babaei, A.A.; Mahvi, A.H.; Mesdaghiniai, A.R.; Nabizadeh, R.; Jaafarzadeh Haghighi, N.; Vaezi, F. (Asian Journal of Chemistry, 2010)
The fundamentals of the photocatalysis based degradation of low concentrations of nonylphenol (NP) an endocrine disrupting compound in batch photoreactor with a UV-visible (UV-Vis) lamp (125 W) and in the presence of ZnO nanocatalyst, under initially environmental conditions and purging oxygen are discussed in this work. The objective of the study is to quantitatively verify the feasibility of nonylphenol degradation with UV-vis/ZnO under such conditions. The conclusions may be potentially helpful to further develop an effective in situ treatment of nonylphenolcontaminated water. Initial nonylphenol concentrations ([NP]0) of 100 to 2000 ppb (ca. 0.454 to 9.08 μM, respectively) were treated with UV-vis/ZnO using different nano-catalyst loading rates. UV-vis illumination alone degraded insignificant amount of nonylphenol, with negligible changes in total organic carbon, whereas in the presence of ZnO, much faster photodegradation of nonylphenol and effective mineralization occurred; 99.4 ±0.45 % and 93.4 ±1.2 % of initial nonylphenol was degraded within 2 h in the experiment at [NP]0 » 0.454 μM and [NP]0 » 9.08 μM, respectively. The degradation rate constant decreased with an increase in the initial concentration of nonylphenol, while it increased with oxygen concentration. The degradation rate also increased with ZnO loading until a concentration of 0.5 g L-1. The degradation rate increased between pH 3.6 and 10, but significantly decreased with increasing pH between 10 and 11.5.